Broun, William. William Broun to Bettie Broun, Northumberland County, VA, February 8, 1863 - Broun, William (Valdosta State University Archives and Special Collections, 2020., 1863)
Camp Gregg February 8, 1863 My Dear Sister, I reached camp last night and found your very welcome letter awaiting my arrival. I have been home & found them all well.
Handwritten letter from William Broun to his sister Bettie Broun. Camp Gregg near Fredericksburg, Virginia, February 8, 1863. 1 page letter on sheet of paper.
Keywords: American Civil War (1861-1865); Broun, Bettie Lee, 1846-1927; Broun, William, Captain, 1842-1908; Personal correspondence; Virginia--Lancaster County; Virginia--Northumberland County; Virginia--Fredericksburg; Virginia